Health Literacy and Associated Factors Patients with Type 2 Diabetes Mellitus in Rural Thailand - Songsin, Niwat; Kaiwong, Krittika; Wangfang, Phurida; Sojisirikul, Yossakorn; Mamayamu, Hafisa; Pianjing, Prisna; Chusuton, Sarayut; Boonchieng, Waraporn (National Journal of Community Medicine, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a chronic disease that poses a significant public health challenge. Effective management requires patients to engage in self-care behaviors, including medication adherence, a healthy diet, and regular blood glucose monitoring. Health literacy plays a crucial role in enabling patients to understand and apply health information, reducing complications, and improving outcomes. This study aims to assess the health literacy of T2DM patients in rural Samut Songkhram Province, Thailand. Methods: This cross-sectional descriptive study involved 403 T2DM patients from Samut Songkhram Province. Data were collected using a health literacy questionnaire assessing knowledge, information access, and decision-making abilities. Participants were selected through multi-stage random sampling, and data were analyzed using descriptive and inferential statistics, including stepwise multiple linear regression. Results: The study revealed that the overall health literacy of patients was low (M = 34.72, SD = 6.28). Three factors significantly predicted health literacy: education level (Beta = 0.427), complications (Beta = 0.316), and occupation (Beta = 0.218). These factors accounted for 58.4% of the variance in health literacy, with statistical significance (R² = 0.584, p <0.05). Conclusion: The study highlights low health literacy among T2DM patients. To address this, public health agencies should implement community-based educational programs, and healthcare providers should offer personalized health education to improve diabetes management and self-care behaviors.